contemporary ijtihad - Yusri Mohamad (ISSI, 2016)
This book examines ijtihad in uts contemporary manifestation with the premise that there is a need to delimit the boundaries and frame work of this process to reduce dispute and allow for focus on more stretegic aspects of ijtihad.